2018
DOI: 10.1039/c8ra07886f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of the ligand controlled regioselectivity in iridium catalyzed C–H borylation of aromatic imines

Abstract: DFT calculation indicates that in iridium catalyzed C–H borylation of aromatics, the ortho selectivity is proposed to be attributed to the electron donating effect of AQ ligand, while the meta selectivity is due to steric hindrance of TMP ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…18 A recent report from Gao, Yao, and co-workers suggested an Ir(I)-Ir(III) catalytic cycle based on DFT calculations. 28 A similar interaction was implicated in the ortho-CH borylation of methylthio-protected phenols and anilines, which was recently reported by Kanai and Kuninobu. 29 Catalyst-enabled Site-selectivity through (i) Attractive Interactions realm of enzymatic catalysis, and also underpin the recent advances in organocatalysis.…”
Section: Chelation-directed Ortho-c-h Borylations By Ligand Modificatsupporting
confidence: 56%
“…18 A recent report from Gao, Yao, and co-workers suggested an Ir(I)-Ir(III) catalytic cycle based on DFT calculations. 28 A similar interaction was implicated in the ortho-CH borylation of methylthio-protected phenols and anilines, which was recently reported by Kanai and Kuninobu. 29 Catalyst-enabled Site-selectivity through (i) Attractive Interactions realm of enzymatic catalysis, and also underpin the recent advances in organocatalysis.…”
Section: Chelation-directed Ortho-c-h Borylations By Ligand Modificatsupporting
confidence: 56%
“…The fourth step is reductive elimination of HBpin to regenerate (NN)­Ir­(Bpin) 3 . The third and fourth steps were reported to occur with a small energy barrier. , This catalytic cycle is essentially the same as that of sp 2 C–H borylation of benzene catalyzed by iridium­(III) triboryl complex. We investigated another possible catalytic cycle consisting of Ir­(I) and Ir­(III) species and found that the Ir­(I)/Ir­(III) catalytic cycle is not likely, as discussed in the Supporting Information (page S25 and Figure S13). This is true because the Ir­(I)/Ir­(III) cycle is possible when bulky diphosphine is used instead of 1,10-phenanthroline derivative for the Ir catalyst …”
Section: Resultsmentioning
confidence: 81%
“…We first investigated iridium-catalyzed sp 3 C–H borylation of THF using DFT. The active species is an iridium­(III) triboryl complex, and the catalytic cycle consists of the C–H activation through oxidative addition of the C–H bond to the iridium­(III) atom and reductive elimination between boryl and oxolanyl groups, which is the same as that proposed for sp 2 C–H borylation of benzene. The reductive elimination of B–C bond is rate-determining step, and the β-regioselectivity is determined at this reductive elimination. The reductive elimination in the β-regioselective borylation occurs through a TS lower in energy than that in the α-regioselective one, and the lower energy TS of the β-regioselective borylation arises from the E int between (phen)­Ir­(Bpin) 2 (H) and oxolanyl···Bpin moieties being larger (more negative) than that in the α-one.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of this intriguing observation was qualitatively attributed to the participation of the imino group on the substrate in the case of the ortho selectivity, whereas electrostatic and secondary interactions between the ligand and the substrate were proposed as responsible for the meta borylation. A recent computational study on the mechanism of this borylation reaction by the Gao and Yao groups attributed the origin of the ortho selectivity to decreased steric and improved electron donation by 8-AQ , while in the case of the TMP ligand, the ortho position is proposed to experience higher steric repulsion between the ligand and the imine . Although their study provided the energetic details of various mechanistic models, explicit data to reconcile the key argument on the differences in steric/electronic effects were not provided, except the Mulliken charges.…”
Section: Introductionmentioning
confidence: 99%
“…A recent computational study on the mechanism of this borylation reaction by the Gao and Yao groups attributed the origin of the ortho selectivity to decreased steric and improved electron donation by 8-AQ, while in the case of the TMP ligand, the ortho position is proposed to experience higher steric repulsion between the ligand and the imine. 12 Although their study provided the energetic details of various mechanistic models, explicit data to reconcile the key argument on the differences in steric/electronic effects were not provided, except the Mulliken charges. Furthermore, the lack of (a) energetic span of the proposed catalytic cycles, (b) the rationalization of the computed energetic differences between the key regiocontrolling transition states (TSs) using methods such as the NCI or distortion interaction/activation strain analyses, and (c) conformational sampling of the N-alkyl groups of the substrate all together preclude definite conclusions on regiochemical preferences.…”
Section: ■ Introductionmentioning
confidence: 99%